2022
DOI: 10.3390/molecules27123696
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Model Characterization of the Electrical Conductivity of PVA/PPy/rGO Nanocomposite

Abstract: Owing to the numerous advantages of graphene-based polymer nanocomposite, this study is focused on the fabrication of the hybrid of polyvinyl alcohol (PVA), polypyrrole (PPy), and reduced graphene-oxide. The study primarily carried out the experimentation and the mathematical analysis of the electrical conductivity of PVA/PPy/rGO nanocomposite. The preparation method involves solvent/drying blending method. Scanning electron microscopy was used to observe the morphology of the nanocomposite. The electrical con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The efficient electron mobility between the graphene electrode active material and electrolyte can be attributed to the electrode's large specific surface area and porosity. 83,84 Graphene oxide, reduced graphene oxide, graphene nanoplatelets, and many others are the various terminologies for graphene. Conductive polymers, on the other hand, are conjugated polymers having exceptional electrical conductivity and redox reaction behavior, low toxicity, and less pollution properties.…”
Section: Nanomaterials Energy Storage Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficient electron mobility between the graphene electrode active material and electrolyte can be attributed to the electrode's large specific surface area and porosity. 83,84 Graphene oxide, reduced graphene oxide, graphene nanoplatelets, and many others are the various terminologies for graphene. Conductive polymers, on the other hand, are conjugated polymers having exceptional electrical conductivity and redox reaction behavior, low toxicity, and less pollution properties.…”
Section: Nanomaterials Energy Storage Systemsmentioning
confidence: 99%
“…Graphene is a carbonaceous material with excellent electrical conductivity, large surface area, high thermal and chemical stabilities, and mechanical strength. The efficient electron mobility between the graphene electrode active material and electrolyte can be attributed to the electrode's large specific surface area and porosity 83,84 . Graphene oxide, reduced graphene oxide, graphene nanoplatelets, and many others are the various terminologies for graphene.…”
Section: Nanomaterials Energy Storage Systemsmentioning
confidence: 99%
“…The datasets for the series-parallel electrical conductivity model were obtained from laboratory experimentation of graphene nanoplatelets loaded-polypyrrole [38] and reduced graphene-oxide loaded polyvinyl alcohol/polypyrrole nanocomposites [39].…”
Section: Materials and Experimentationmentioning
confidence: 99%
“…Recently, ternary Ni-Co sulfides with rich redox-active sites and variable valence states, such as Ni 2+ /Ni 3+ , Co 2+ /Co 3+ , and Co 3+ /Co 4+ , during the charging and discharging process have been suggested as promising battery-type materials for supercapatteries; however, the low conductivity, easy agglomeration, and poor electrochemical stability of ternary Ni-Co sulfides present a series of problems to be tackled [ 6 , 7 ]. Many results have reported that the combination of high conductivity materials, such as reduced graphene oxide (rGO) or graphene (G) and Ni-Co sulfides using a hydrothermal process, can achieve a synergistic effect, leading to enhanced electrochemical performance [ 8 , 9 , 10 , 11 , 12 ]. Dong et al [ 9 ] prepared Ni x Co y S 4 nanosheets (various Ni-Co ratios) on rGO using a hydrothermal method, and found that the Ni 1.64 Co 2.40 S 4 /rGO electrode delivers a high specific capacitance of 1089 F g −1 at 1 A g −1 .…”
Section: Introductionmentioning
confidence: 99%